Penguatan metode deteksi dini faktor risiko dalam keluarga sebagai upaya pencegahan stunting pada tim pendamping keluarga di desa lokus - Rachmawati, Rachmawati; Iskandar, Iskandar; Al Rahmad, Agus Hendra; Fadjri, T Khairul; Hidayat, Taufik (Jurnal PADE: Pengabdian & Edukasi, 2024)
The issue of stunting is one of the double burdens of malnutrition (DBM) due to growth and development failures in children, which have adverse effects both in the short and long term. This community service activity aims to enhance the knowledge and skills of cadres and Family Companion teams to conduct early detection of risk factors and control efforts to support the acceleration of stunting reduction programs at the village level, as well as collaboratively with the Team and the government in determining priority target families. The training aimed at improving cadres and family assistance teams was held on July 16, 2024, targeting village heads, village secretaries, family assistance team members, village PKK elements, and posyandu cadres from Mee Tanoh and Dayah Muara Villages, totaling 25 people, at the Mee Tanoh village hall, Peukan Baro District, Pidie Regency.   The results of the activity show that there was an increase in participants' knowledge after the training, with an improvement of 38.1 points from the previous average score of 53.1, rising to 78.1. This training activity can enhance the knowledge and skills of village assistance teams and posyandu cadres in screening families at risk of stunting to receive independent family assistance as an effort to reduce stunting at the village level.